Analysis Of The Efficiency And Effectiveness Of Village Budget Management In Temiang Village, Pagar Jati Regency, Central Bengkulu District - Aprilia Azari; Neri Susanti; Tito Irwanto (Penerbit Jurnal Indonesia, 2023)
This research aims to analyze the level of efficiency and effectiveness of village fund budget management in Temiang village, Pagar Jati District, Central Bengkulu Regency, whether it is used efficiently in Temiang village and whether it is effective, and to find out what the level of efficiency and effectiveness of village fund budget management is.The results of the research show that budget and village management in Temiang Village, Pagar Jati District, Central Bengkulu Regency is less efficient and less effective.